Impact of the Tourism Sector on the Socio-Economy of Indigenous People on The Islands Around Semporna - Yusoh Mohamad Pirdaus; Kumalah Mohd Jirey; Abdul Latip Normah; Hussin Rosazman; Zakaria Zulayti; Jamru Lindah Roziani; Hanafi Nurhazliyana; Samsul Syafiqah Syuhada; Pingking Andreas (BIO Web of Conferences, 2023)
The natural beauty of the islands is the main attraction of the tourism sector in Semporna, Sabah. The development of this tourism industry is seen to have a positive impact on the overall development in the Semporna District. However, whether this tourism development has a positive impact on the socio-economic development of the indigenous people in the surrounding islands of Semporna is the primary focus of this pilot study. The objective of this study is to identify the impact of tourism on the socio-economic development of the indigenous communities in the surrounding islands of Semporna. The study adopts a quantitative approach involving 60 respondents, with 20 respondents in each study location. The study locations include three islands around Semporna: Larapan Island, Omadal Island, and Mabul Island. The results of the study found that the respondents strongly agreed that the arrival of tourists in Semporna increased the income of the island's residents and provided job opportunities for the local population, with a minimum mean value of 4.6 for both aspects. In the social aspect, the majority of community members were highly responsive and believed that tourism empowered women's involvement (mean=4.4) and strengthened cooperation among community members (mean=4.6). In conclusion, the development of tourism in Semporna has a positive impact on the socio-economic development of the indigenous communities in the surrounding islands. However, various initiatives need to be strengthened to ensure that this positive impact benefits a larger number of indigenous people and helps alleviate poverty issues among the indigenous communities, particularly on the islands.